Treatment of Xanthelasma Palpebrarum using a pulsed dye laser: a prospective clinical trial in 38 cases - Karsai, Syrus; Czarnecka, Agnieszka; Raulin, Christian (Dermatologic surgery, 2010)
Several studies have reported positive results of nonablative laser treatment of xanthelasma palpebrarum, but the published evidence is weak and inconclusive. To systematically evaluate the effect of pulsed dye laser (PDL) treatment of xanthelasmas.